ph2a_hw9_soln

ph2a_hw9_soln - Quiz Problem 5 Solution Problem 3 Solution...

Info iconThis preview shows pages 1–11. Sign up to view the full content.

View Full Document Right Arrow Icon
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 4
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 6
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 8
Problem 3 Solution a) The condition that the wavefunction is normalized is: 1 = Z 0 | ψ ( x ) | 2 dx = Z 0 | A | 2 ± x x o ² 2 b e - 2 x/x o dx = | A | 2 x o 2 b Z 0 x 2 b e - 2 x/x o dx Using the hint (with a = 2 /x o ), this is equal to: = | A | 2 x o 2 b (2 b )! (2 /x o ) 2 b +1 = | A | 2 (2 b )! x o 2 2 b +1 For this to equal one, we must take (picking the phase of A so it’s real and positive): A = s 2 2 b +1 (2 b )! x o b) By definition: < x m > = Z 0 x m | ψ ( x ) | 2 dx = Z 0 x m | A | 2 ± x x o ² 2 b e - 2 x/x o dx = | A | 2 x o 2 b Z 0 x 2 b + m e - 2 x/x o dx = | A | 2 x o 2 b (2 b + m )! (2 /x o ) 2 b + m +1 Using the value of A we calculated above: 1
Background image of page 9

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
= 2 2 b +1 (2 b )! x o 1 x o 2 b (2 b + m )! (2 /x o ) 2 b + m +1 = (2 b + m )! (2 b )! ± x o 2 ² m c) We have: Δ x = p < x 2 > - < x > 2 Using the result from the last part: = s (2 b + 2)! (2 b )! ± x o 2 ² 2 - ³ (2 b + 1)! (2 b )! x o 2 ´ 2 = x o 2 p (2 b + 2)(2 b + 1) - (2 b + 1) 2 = x o 2 p (2 b + 1) ((2 b + 2) - (2 b + 1)) = x o 2 2 b + 1 d) The time-independent Schrodinger equation is: - ¯ h 2 2 m d 2 ψ dx 2 ( x ) + V ( x ) ψ ( x ) = ( x ) Rearranging: ¯ h 2 2 m d 2 ψ dx 2 ( x ) = ( V ( x ) - E ) ψ ( x ) In this case, it’s easy to compute: d 2 ψ dx 2 ( x ) = A ³ x x o ´ b ³ b ( b - 1) x 2 - 2 b xx o + 1 x o 2 ´
Background image of page 10
Background image of page 11
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 01/28/2011 for the course PH 2 taught by Professor Dudko during the Spring '09 term at UCSD.

Page1 / 11

ph2a_hw9_soln - Quiz Problem 5 Solution Problem 3 Solution...

This preview shows document pages 1 - 11. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online